REVIEW: HERBAL POTENTIAL IN THE USE OF SPF 30 AND 50 SUNSCREENS - Siti Fatimah Sultan; Nina Salamah (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
Sunscreen is a substance that can reflect or absorb light, protecting the skin from damage caused by exposure to UV radiation. Soursop juice extract (Annona muricata L.), lime peel extract (Citrus aurantifolia), shallot skin extract (Allium cepa L.), celery leaf extract (Apium graveolens L.), and ethanol extract of kersen leaves (Muntingia calabura) are some plants that can be used as natural sunscreens. According to the SPF value and the protective power category, the soursop juice extract has an SPF value of 5.188, 12.242, and 17.247. Lime peel extract has SPF values of 28.6, 42.2, and 81.8 (max-ultra). Onion peel extract has SPF values of 11.4, 20.12, 31.8, and 34.83 (max-ultra). Celery leaf extract had SPF values of 1.7873, 4.5553, 7.3183, and 8.1573 (max-ultra). Kersen leaf ethanol extract had concentrations of 1.528, 3.890, 3.971, 4.585, and 5.252 (max-ultra). Phenolic components, polyphenols, flavonoids, tannins, and vitamin C are known as bioactive compounds in the five plant extracts that function as sunscreens. The polarity of the solvent influenced the SPF rating and protective power category. It is concluded that the SPF value and protective power of the plant extracts have SPF values and protective power categories with extracts in ultra categories. The bioactive compounds contained in the five plant extracts that act as sunscreens are phenolic compounds, polyphenols, flavonoids, tannins, and vitamin C ...